Extent of hypoattenuation on CT angiography source images in basilar artery occlusion: prognostic value in the Basilar Artery International Cooperation Study - Pütz, Volker; Khomenko, Andrei; Hill, Michael D.; Dzialowski, Imanuel; Michel, Patrik; Weimar, Christian; Wijman, Christine A. C.; Mattle, Heinrich P.; Engelter, Stefan T.; Muir, Keith W.; Pfefferkorn, Thomas; Tanne, David; et al. (Stroke, 2011)
BACKGROUND AND PURPOSE: The posterior circulation Acute Stroke Prognosis Early CT Score (pc-ASPECTS) quantifies the extent of early ischemic changes in the posterior circulation with a 10-point grading system. We hypothesized that pc-ASPECTS applied to CT angiography source images predicts functional outcome of patients in the Basilar Artery International Cooperation Study (BASICS). - METHODS: BASICS was a prospective, observational registry of consecutive patients with acute symptomatic basilar artery occlusion. Functional outcome was assessed at 1 month. We applied pc-ASPECTS to CT angiography source images of patients with CT angiography for confirmation of basilar artery occlusion. We calculated unadjusted and adjusted risk ratios (RRs) of pc-ASPECTS dichotomized at ≥8 versus <8. Primary outcome measure was favorable outcome (modified Rankin Scale scores 0-3). Secondary outcome measures were mortality and functional independence (modified Rankin Scale scores 0-2). - RESULTS: Of 158 patients included, 78 patients had a CT angiography source images pc-ASPECTS≥8. Patients with a pc-ASPECTS≥8 more often had a favorable outcome than patients with a pc-ASPECTS<8 (crude RR, 1.7; 95% CI, 0.98-3.0). After adjustment for age, baseline National Institutes of Health Stroke Scale score, and thrombolysis, pc-ASPECTS≥8 was not related to favorable outcome (RR, 1.3; 95% CI, 0.8-2.2), but it was related to reduced mortality (RR, 0.7; 95% CI, 0.5-0.98) and functional independence (RR, 2.0; 95% CI, 1.1-3.8). In post hoc analysis, pc-ASPECTS dichotomized at ≥6 versus <6 predicted a favorable outcome (adjusted RR, 3.1; 95% CI, 1.2-7.5). - CONCLUSIONS: pc-ASPECTS on CT angiography source images independently predicted death and functional independence at 1 month in the CT angiography subgroup of patients in the BASICS registry.